The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1515/cclm-2017-0397
|View full text |Cite
|
Sign up to set email alerts
|

Hair testing of GHB: an everlasting issue in forensic toxicology

Abstract: Background: In this paper, the authors present a critical review of different studies regarding hair testing of endogenous γ-hydroxybutyrate (GHB), concentrations in chronic users, and values measured after a single GHB exposure in drug facilitated sexual assault (DFSA) cases together with the role of a recently identified GHB metabolite, GHB-glucuronide. Content:The following databases (up to March 2017) PubMed, Scopus and Web of Science were used, searching the following key words: γ-hydroxybutyrate, GHB, GH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 29 publications
(101 reference statements)
0
31
0
1
Order By: Relevance
“…Owing to the dual nature of GHB, endogenous metabolite and recreational drug of abuse, major efforts have been exerted to establish endogenous concentrations in hair to serve as baseline levels [121]. Studies have shown that GHB concentrations in hair vary in relation to hair color and ethnicity and are usually in the range 0-5 ng/mg [121].…”
Section: Hairmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the dual nature of GHB, endogenous metabolite and recreational drug of abuse, major efforts have been exerted to establish endogenous concentrations in hair to serve as baseline levels [121]. Studies have shown that GHB concentrations in hair vary in relation to hair color and ethnicity and are usually in the range 0-5 ng/mg [121].…”
Section: Hairmentioning
confidence: 99%
“…Owing to the dual nature of GHB, endogenous metabolite and recreational drug of abuse, major efforts have been exerted to establish endogenous concentrations in hair to serve as baseline levels [121]. Studies have shown that GHB concentrations in hair vary in relation to hair color and ethnicity and are usually in the range 0-5 ng/mg [121]. The first segment of hair closest to the scalp should not be used in the analysis of GHB, because of a possible contamination with sweat, which can elevate endogenous concentrations in hair up to 20 ng/mg hair [122].…”
Section: Hairmentioning
confidence: 99%
“…Physiological GHB concentrations were measured in all segments ranging between 0.2 and 0.7 ng/mg, which discards the involvement of this drug in this presumed DFSA, as recently shown by Busardo et al Five compounds – 4‐MEC, MDPV, doxylamine, tramadol, and mepivacaine – were found by LC–MS/MS. 4‐MEC, MDPV and doxylamine were detected in the first segment (A, 0–1 cm) at very low concentrations of 3, 5 m and 9 pg/mg, respectively (Figure ), while not being detected in the 2 following segments (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…When she realizes the situation, it gets too late to investigate the drug used in crime from urine or blood (Dinis-Oliveira and Magalhães 2013; LeBeau and Montgomery 2010). Different drugs, e.g., ketamine, rohypnol, and GHB are used for the crime (Busardò et al 2018). Drugs used for DFSA are converted to metabolites, so their presence cannot be detected in urine or in blood.…”
Section: Applications Of Hair Analysis Drug-facilitated Sexual Assaultsmentioning
confidence: 99%